Strategi Pemasaran Toko Meidy Fashion dalam Mempertahankan Bisnis pada Masa Pandemi Covid-19 - Monik; Siregar, Onan Marakali (Regress: Journal of Economics & Management, 2022)
This article aims to analyze Meidy Fashion Store's marketing strategy in maintaining business during the Covid-19 pandemic. In addition, this study also aims to analyze the supporting and inhibiting factors of the Meidy Fashion Store marketing strategy in maintaining business during the Covid-19 pandemic. This research is a type of descriptive qualitative research that presents an analysis of the Meidy Fashion Store marketing strategy in maintaining business during the Covid-19 pandemic. The results showed that the marketing strategy carried out by the Meidy Fashion Store was through a product strategy, namely making product innovations by selling clothes that were needed at this time. The pricing strategy is to give discounts. The place strategy is switching to online sales and promotion strategies by utilizing social media. The inhibiting factors for Meidy Fashion's marketing strategy are the presence of competitors who sell the same product but at a price far below this store's product, the scarcity and increase in the price of raw materials from producers, market closing policies, and the information provided is not conveyed properly to customers. The supporting factors for Meidy Fashion's marketing strategy are by always maintaining the characteristics and quality of the products sold to customers, providing promos in the form of price discounts, and evaluating published advertisements so that information is conveyed properly to customers.